Analisis Minat Mahasiswa Pendidikan Olahraga dan Kesehatan Universitas Jambi Angkatan 2024 terhadap Permainan Olahraga Pickleball - ⁠M. Alhariq HS; Ali, Muhammad; Decheline, Grafitte (MAN Insan Cendekia Jambi, 2025)
This research aims to analyze the interest of 2024 Physical Education and Health students at Universitas Jambi toward the sport of pickleball. Pickleball is a sport that combines elements of tennis, badminton, and table tennis that is relatively new in Indonesia. The research method employed a quantitative descriptive approach with data collection through questionnaires. The research population consisted of 171 students from 5 classes, with a total sampling technique. The research instrument was a questionnaire comprising 40 statements with indicators of intrinsic factors (interest, attention, needs) and extrinsic factors (role of coaches, facilities, family, environment). The research results show that overall student interest falls into the medium category (59%), with intrinsic factors in the medium category (46.7%) and extrinsic factors also in the medium category (60.2%).